Management of a child with reactive attachment disorder in the dental clinical setting : a case report = Manejo de un niño con trastorno de apego reactivo en el entorno clínico dental : reporte de un caso - Garrocho Rangel, Arturo 1961-
Reactive attachment disorder (RAD) is an early childhood mental health disease characterized by impaired social interactions and communication abilities, and neurological deficits in the child's developing brain. This disorder can significantly affect the pediatric patient's behavior in the dental setting. An uncooperative 9-year-old Mexican girl, who was residing in a temporary home, was referred by a general dental practitioner to the Postgraduate Pediatric Dental Clinic with her caretaker, requesting dental examination and treatment. The patient presented with a previous diagnosis of RAD with intellectual/social disability. With the psychiatrist's guidance, an exhaustive oral prophylaxis was carried out in the initial appointments, followed by diverse restorative treatments under the continuous application of behavioral management techniques. These restorative procedures included resin restorations and pit-fissure sealants, under local anesthesia and rubber-dam isolation, on the first four permanent molars. The entire treatment was completed in six weeks. The patient and her caretaker were provided with detailed educational and motivational strategies for improving the patient ́s oral hygiene, and they also received nutritional advice. For control reviews and the reinforcement of preventive habits, future appointments were carefully scheduled. An interdisciplinary pediatric collaboration between the dentist, nurse, and psychiatrist was fundamental for improving the patient's oral health and general welfare.